Victimisation, Well‐being and Compensation: Using Panel Data to Estimate the Costs of Violent Crime. (20th July 2017) - Johnston, David W.; Shields, Michael A.; Suziedelyte, Agne
Abstract: The costs of violent crime victimisation are often left to a tribunal, judge or jury to determine, which can lead to considerable subjectivity and variation. Using panel data, this article provides compensation estimates that help reduce the subjectivity of awards by providing a benchmark for the compensation required to offset direct and intangible costs. Individual‐area fixed‐effects models of well‐being that allow for adaptation and the endogeneity of income suggest that, on average, A$88, 000 is required to compensate a violent crime victim, with the amount being greater for females (A$102, 000) than males (A$79, 000).